Research on Accurate Impact Point Prediction Methods of Heavy Rocket Debris. Issue 1 (February 2021) - Tao, Liu; Chao, Kou; Li, Ma; Jing, Yang; yuchao, Wang; Yu, Zhao
Abstract: Driven by the demands of rocket launching safety and major scientific research projects, this study probes into the process of impact point prediction for heavy debris from rocket launching. By establishing the basic model of impact point prediction, an analysis of error sources of impact point prediction is conducted to define the research direction of improving the accuracy of impact point prediction. The calculation model of heavy debris impact points introduces the concept of comprehensive analysis of big data. Based on the current situation of equipment, it makes full use of valuable measured data resources of rocket launching and the data information of the measured flight and landing area in multiple samples. Using statistical methods, a back calculation of air resistance and velocity correction affecting the impact point calculation is made, thus forming an accurate calculation model of heavy debris impact points. The data validation shows that the real-time prediction accuracy of this model has been greatly improved compared with the original model, which meets the research expectations.